2008
DOI: 10.1021/es071893z
|View full text |Cite
|
Sign up to set email alerts
|

National-Level Infrastructure and Economic Effects of Switchgrass Cofiring with Coal in Existing Power Plants for Carbon Mitigation

Abstract: We update a previously presented Linear Programming (LP) methodology for estimating state level costs for reducing CO 2 emissions from existing coal-fired power plants by cofiring switchgrass, a biomass energy crop, and coal. This paper presents national level results of applying the methodology to the entire portion of the United States in which switchgrass could be grown without irrigation. We present incremental switchgrass and coal cofiring carbon cost of mitigation curves along with a presentation of regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A fraction of the coal used as fuel in existing steam turbine plants can be substituted by either cofiring biomass with coal or by using 100% biomass, by retrofitting the boiler to allow biomass input. 17 Retrofitting results in a small (assumed 10%) loss of efficiency. The costs of retrofitting are discussed in the section that follows.…”
Section: ■ Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A fraction of the coal used as fuel in existing steam turbine plants can be substituted by either cofiring biomass with coal or by using 100% biomass, by retrofitting the boiler to allow biomass input. 17 Retrofitting results in a small (assumed 10%) loss of efficiency. The costs of retrofitting are discussed in the section that follows.…”
Section: ■ Data and Methodsmentioning
confidence: 99%
“…In the electricity sector, biomass has the potential to displace coal. A fraction of the coal used as fuel in existing steam turbine plants can be substituted by either cofiring biomass with coal or by using 100% biomass, by retrofitting the boiler to allow biomass input . Retrofitting results in a small (assumed 10%) loss of efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analyses have shown that, in order to achieve high levels of emissions reductions at minimal additional cost, transportation of biomass over significant distances should be avoided and local biomass resources should be considered for regional energy needs such as electricity [6]. Numerous studies have explored the use of biomass resources, including forest residues and dedicated crops like switchgrass, for co-firing with coal in power plants with an emphasis on local resources [2,7,8].…”
Section: Introductionmentioning
confidence: 99%